Mechanical Properties of Polypropylene Composites Containing Polymer Fibers - Md Ali, Mohd Amran; Raja, Izamshah; Abu Bakar, Mohd Hadzley; Sivarao, Subramonian; Hussein, Nur Izan Syahriah (Universiti Teknikal Malaysia Melaka, 2012)
The mechanical properties of polypropylene composites containing polytetrafluoroethylene polymer-fibers (PPF) were studied. The main objective was to study the affected of PPF in mechanical properties in solid state. Both polypropylene (PP) and PPF were compounded using twin screw extruder and prior to the mechanical test, the test specimens were formed by injection molding machine and compression molding machine. After forming the dog bone, rectangular bar, circular plate and flat sheet, the test specimens were prepared for tensile test (ASTM D638), flexural test (ASTM D790), impact test (ASTM D256), compression test (ASTM D695) and hardness test (ASTM D785). Hardness test shown similar value for both PP and PP with PPF. The study has demonstrated that PP compound with PPF shown increased in tensile, flexural, impact and compression strength, however similar value in hardness strength.